Pemodelan dan Animasi Ikan Dalam Simulasi Akuarium Maya - Ricki Effendy; Meilany Dewi; Erwin Setyo Nugroho (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2011)
Computer technology developed rapidly could be used to visualize the real world, which could be developed for observation for research, learning, game development and so on. As an ecosystem with clear limited space, aquarium with various types of creatures living in it was a quite easy ecosystem to be visualized compared with other ecosystems. As an early stage of visualization, modeling was performed to a fish, as a creature in aquarium, with Belida Jawa as the focused type. By utilizing the principles and techniques of edge detection on Computer Vision, datas of form and movements of the fish in several frames of video data was processed before the manual measurement performed. Using the measurement data and Polinom Lagrange, equations of the fish’s body form and movements was formed. The equations was then tested by modeling the fish, either the form or movements, in 3D. The modeling was performed using Blender, where there was a Belida Jawa fish in the aquarium. In the testing stage, modeling using the equations obtained could be done. Furthermore, by using edge detection technique to process the data, the measurement was done more definitely and objectively. Keywords: Visualization, Modeling, Belida Jawa Fish